Daphnetin attenuates LPS‐induced osteolysis and RANKL mediated osteoclastogenesis through suppression of ERK and NFATc1 pathways. Issue 10 (27th February 2019) - Wu, Zuoxing; Wu, Hailun; Li, Chen; Fu, Fangsheng; Ding, Jiaxin; Shao, Siyuan; Li, Kai; Yu, Xiao; Su, Yuangang; Liang, Jiamin; Lin, Xixi; Yuan, Guixin; et al.
Abstract: Aseptic prosthetic loosening and periprosthetic infection resulting in inflammatory osteolysis is a leading complication of total joint arthroplasty (TJA). Excessive bone destruction around the bone and prosthesis interface plays a key role in the loosening prostheses leading to revision surgery. The bacterial endotoxins or implant‐derived wear particles‐induced inflammatory response is the major cause of the elevated osteoclast formation and activity. Thus, agents or compounds that can attenuate the inflammatory response and/or inhibit the elevated osteoclastogenesis and excessive bone resorption would provide a promising therapeutic avenue to prevent aseptic prosthetic loosening in TJA. Daphnetin (DAP), a natural coumarin derivative, is clinically used in Traditional Chinese Medicine for the treatment of rheumatoid arthritis due to its anti‐inflammatory properties. In this study, we report for the first time that DAP could protect against lipopolysaccharide‐induced inflammatory bone destruction in a murine calvarial osteolysis model in vivo. This protective effect of DAP can in part be attributed to its direct inhibitory effect on RANKL‐induced osteoclast differentiation, fusion, and bone resorption in vitro. Biochemical analysis found that DAP inhibited the activation of the ERK and NFATc1 signaling cascades. Collectively, our findings suggest that DAP as a natural compound has potential for the treatment of inflammatory osteolysis. Abstract : Daphnetin (DAP) is a natural coumarin that could protect against lipopolysaccharide‐induced inflammatory bone destruction in a murine calvarial osteolysis model in vivo. This protective effect of DAP can in part be attributed to its direct inhibitory effect on RANKL‐induced osteoclast differentiation, fusion, and bone resorption in vitro. Biochemical analysis found that DAP inhibited the activation of the ERK and NFATc1 signaling cascades.